Evaluation of Occupational Needlestick-Sharp Injuries and Status of Hepatitis B Immunization on Nurses Working at Malatya Province Hospitals - Omac, Mehtap; Egri, Mucahit; Karaoglu, Leyla (Annals of Medical Research, 2021)
None
Keywords: Needlestick-Sharp Injuries, Nurses, Hepatit B